Conference interpreting explained - Jones, Roderick. (St. Jerome Pub., 2002)
The book concludes with a comment on the pleasure of conference interpreting, as well as a glossary and suggested further readings. In all, it fills a major gap in English-language publications on interpreting, providing an introduction for beginners, a down-to-earth guide for students, and a handy compendium for teachers.